Improvements in clinical pain and experimental pain sensitivity after cognitive functional therapy in patients with severe persistent low back pain. (January 2020) - Vaegter, Henrik Bjarke; Ussing, Kaper; Johansen, Jannick Vaaben; Stegemejer, Irene; Palsson, Thorvaldur Skuli; O'Sullivan, Peter; Kent, Peter
Abstract: Introduction: Multidisciplinary care is recommended for disabling persistent low back pain (pLBP) nonresponsive to primary care. Cognitive functional therapy (CFT) is a physiotherapy-led individualised intervention targeting psychological, physical, and lifestyle barriers to recovery, to self-manage pLBP. Objectives: This pilot study investigated clinical outcomes and pain thresholds after a 12-week CFT pathway in patients with severe pLBP referred to a University Pain Center. Exploratory analyses compared changes in clinical outcomes, opioid consumption, and costs after CFT with changes after a multidisciplinary pain management (MPM) pathway. Methods: In total, 47 consecutively referred pLBP patients consented to the CFT pathway. At baseline, 3 and 6 months, clinical outcomes and PPTs were assessed. Control patients (n = 99) who had completed an MPM pathway in the last 3 years were matched from the clinical pain registry used in the Pain Center in a 3:1 ratio based on propensity scores derived from relevant baseline variables of the CFT cases. Results: Most clinical outcomes and low back pressure pain threshold were improved at 3 and 6 months after the CFT pathway. Compared with MPM, CFT patients had significantly larger reductions in disability and improved quality of life after the interventions at a lower cost (−3688[Euro sign] [confidence interval: −3063 to −4314[Euro sign]]). Reduction in pain intensity and proportion of patients withdrawing from opioids (18.2% vs 27.8%) were similar between CFT and MPM groups. Conclusion: Improvements in clinical and experimental pain were found after the CFT pathway. Fully powered randomized controlled trials comparing CFT with an MPM program in patients with disabling pLBP are warranted to control for the current limitations.